Tumor Regression Grading Assessment in Locally Advanced Pancreatic Cancer After Neoadjuvant FOLFIRINOX: Interobserver Agreement and Prognostic Implications - Cacciato Insilla, Andrea; Vivaldi, Caterina; Giordano, Mirella; Vasile, Enrico; Cappelli, Carla; Kauffmann, Emanuele; Napoli, Niccolò; Falcone, Alfredo; Boggi, Ugo; Campani, Daniela (Frontiers in Oncology, 2020)
Neoadjuvant therapy represents an increasingly used strategy in pancreatic cancer, and this means that more pancreatic resections need to be evaluated for therapy effect. Several grading systems have been proposed for the histological assessment of tumor regression in pre-treated patients with pancreatic cancer, but issues like practical application, level of agreement and prognostic significance are still debated. To date, a standardized and widely accepted score has not been established yet. In this study, two pathologists with expertise in pancreatic cancer used 4 of the most frequently reported systems (College of American Pathologists, Evans, MD Anderson, and Hartman) to evaluate tumor regression in 29 locally advanced pancreatic cancers previously treated with modified FOLFIRINOX regimen, to establish the level of agreement between pathologists and to determine their potential prognostic value. Cases were additionally evaluated with a fifth grading system inspired to the Dworak score, normally used for colo-rectal cancer, to identify an alternative, relevant option. Results obtained for current grading systems showed different levels of agreement, and they often proved to be very subjective and inaccurate. In addition, no significant correlation was observed with survival. Interestingly, Dworak score showed a higher degree of concordance and a significant correlation with overall survival in individual assessments. These data reflect the need to re-evaluate grading systems for pancreatic cancer to establish a more reproducible and clinically relevant score.